Study of building energy index in Universiti Tun Hussein Onn Malaysia - Noranai, Zamri (UniversityPublications.net, 2012)
Towards year 2020 energy requirement will become more intensive in Malaysia. Building sector is the major energy consumers where is consume 48% of the total electricity energy. According to MS1525 standard, recommended building energy index in Malaysia is 135kWh/m²/yr. However, almost of the building do not meet this standard. Building owners or building user are not aware whether their building achieved or not this requirement. Malaysia presently only three building achieved this standard. The question is do University Tun Hussien Onn achieve this recommended standard? This study is to calculate and identify the building energy index in university. In this project, the case study will focus on the building energy index for major buildings in main campus. The objective of the study can be achieved by sequence of method such as collect energy consume data from energy utility provider, collect gross floor area of the building, calculating building index by excel software and analysis trend of building energy index. It is expected to getting building energy index for year 2010 and 2011 and both of the result will be compared either the trend increasing or decreasing. It estimated the result will not satisfied the MS 1525 Malaysian Standard, but this result will able to build up awareness of building energy index among building owner and users.